Dampak Covid-19 Terhadap Aktivitas Dan Kinerja Mahssiswa Universitas Bengkulu - Purmini, Purmini; Armelly, Armelly (Universitas Bengkulu, 2023)
The objectives of this study are: 1. To find out the description of student activities during the covid19 pandemic, 2. To analyze the impact of the COVID-19 pandemic on student academic performance. The number of respondents in this study were 400 students, using purposive random sampling method, taken as many as 2.5 percent of students from 8 faculties at Bengkulu University. The data were analyzed descriptively and statistically by using Wilcoxon Signed Rank Test. The results of the study found that there were differences in student activities before the pandemic to the pandemic period. During the pandemic the time spent for reading lecture material decreased, while the time spent for doing assignments increased. Working students also increased during the pandemic. Advantages of online lectures: a) saving on transportation costs; b) more technology literate; c) cost-effective appearance; d) more independent in learning; e) keep up with the times; f) saving on the cost of renting a boarding room. Constraints of online lectures: a) Inadequate/unstable internet network; b) Difficulty understanding the material; c) Limited quota owned; d) difficult to adjust lecture time; e) the home environment does not support online lectures; f) inadequate gadgets or hardware. The impact of the pandemic on student academic performance: i). from the aspect of the semester achievement index (IPS), in general it increased in all faculties, the average IPS increased from 3.35 to 3.45. ii). From the aspect of learning independence, on average it increased from good enough to good, iii). However, from the aspect of understanding the lecture material, on average there was a decrease from good (scale value 4.09 out of 5) to not good (scale value 2.57 out of 5). Statistical testing also supports a significant difference in student performance between before the Covid19 pandemic and during the Covid19 pandemic. In terms of semester achievement index (IPS) and learning independence, both increased, but in terms of material understanding decreased. There is a discrepancy between the GPA and students' understanding of the course material Keywords: Student activities1, student performance2, covid19 pandemic3, online lectures4, Wilcoxon Signed Rank Test 5